ANALYSIS OF GENETIC DIVERSITY IN LEGUMES GERMPLASM USING RETROTRANSPOSON BASED MOLECULAR MARKERS - Khapilina , O.N.; Daniyarov , A.Z.; Аmenov А.А.; Novakovskaya А.P.; Тurzhanova А.S.; Тagimanova D.S.; Filippova , N.I.; Каlendar R.N. (Eurasian Journal of Applied Biotechnology, 2017)
Retrotransposon-based molecular markers were used to assess variation in the perennial legumes alfalfa, sweet clover, and lupin from local (Kazakhstan) and world gene pools. Specific retrotransposons were found for species in the Fabaceae family. Conserved regions of LTR retrotransposon sequences were used to design PCR primers to detect polymorphisms by the IRAP method. Universal primers for retrotransposon primer binding site (PBS) sequences were also used. A preliminary screen was used to select the most informative primers that identified up to 80% of polymorphisms. Cluster analysis was carried out to quantify polymorphism and divergence. LTR primers can be used for the simultaneous detection of polymorphic loci that are distributed evenly across the genome. In addition, the study of genetic polymorphism using retrotransposons is distinguished with availability and informative of the method. LTR retrotransposons were employed to study genetic variability and were able to separate the perennial legume varieties according to their relationships and genetic diversity. The results obtained using this method provides a basis for better control of germplasm, future systematic studies, and genetic improvement. This method can also be applied to thestudy of the role of retrotransposons in the genetic variability of species and the dynamics of their genomes.